THERAPEUTIC APPROACH IN EXTENSIVE BURN INJURIES - Vania Anastasova; Elean Zanzov; Karina Ivanova; Petar Kiskinov; Elena Krasteva; Biser Ivanov (Journal of IMAB)
Introduction: burns are the fourth most common trauma. Regardless of the percentage, all burns require specialised treatment. Burns over 20% of total body surface area/ТBSA/ in adults and over 10% in children are called extensive. They require fluid resuscitation and surgical treatment. It is believed that tissue destruction, combined with capillary dysfunction and a pronounced inflammatory response, lead to the development of hypovolemia and thermal shock. The goal: to validate a protocol for the treatment of extensive burns, including first aid, fluid resuscitation treatment, surgical interventions, rehabilitation, and care for the consequences of burns. Material and methods: we tracked and compared the extensive burns of two random years, demographics, treatment types and outcome of it. Discussion: treatment of thermal shock includes proper initial assessment, timely infusion therapy, early surgical treatment and wound covering, rehabilitation and active surveillance. For the outcome of the treatment, the general condition of the patient, the type and depth of the burn, as well as the time of starting the surgical treatment are important. These factors determine the outcome of the treatment, the development of cicatricial tissue and the preservation of the physiological capacity of motion. Conclusion: extensive burns are a challenge for both plastic surgeons and anesthesiologists. The therapeutic approach follows a certain algorithm depending on many factors.